2017
DOI: 10.1177/2047487317738594
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption and cardiorespiratory fitness in five population-based studies

Abstract: Background Poor cardiorespiratory fitness is a risk factor for cardiovascular morbidity. Alcohol consumption contributes substantially to the burden of disease, but its association with cardiorespiratory fitness is not well described. We examined associations between average alcohol consumption, heavy episodic drinking and cardiorespiratory fitness. Design The design of this study was as a cross-sectional population-based random sample. Methods We analysed data from five independent population-based studies (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…We observed higher CRF among women with high levels of alcohol consumption. A study investigating the association between alcohol consumption and CRF based on five independent population-based studies from the US and Germany (including DEGS1) found an inverse u-shaped association with higher fitness levels among moderately drinking men and women 15 . However, these findings are in line with the results of our study, as Baumeister et al observed a maximum of the curve at a very high level of consumption among women (ca.…”
Section: Discussionmentioning
confidence: 99%
“…We observed higher CRF among women with high levels of alcohol consumption. A study investigating the association between alcohol consumption and CRF based on five independent population-based studies from the US and Germany (including DEGS1) found an inverse u-shaped association with higher fitness levels among moderately drinking men and women 15 . However, these findings are in line with the results of our study, as Baumeister et al observed a maximum of the curve at a very high level of consumption among women (ca.…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of chronic alcohol abuse have been well-documented in the setting of established, long-term health conditions such as cardiovascular disease [ 1 ], respiratory distress [ 2 ], gastrointestinal dysfunction, alcoholic liver disease [ 3 6 ], cancer [ 7 ], and metabolic dysfunction [ 8 ]. Excessive alcohol consumption not only causes initial injury via direct toxic effects (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The association of alcohol with physical exercise or cardiovascular fitness is not well known, but a cross-sectional analysis of five population based studies showed that moderate drinkers (10 g alcohol/ day) displayed higher peak oxygen uptakes than abstainers and subjects with higher alcohol intake. 7 This finding may reflect socioeconomic class as the alcohol consumption pattern may differ according to social situation. 8 The effects of these two main confounders can be minimized in a randomized trial.…”
Section: Alcohol Protects Against Ischaemic Heart Disease But Nothinmentioning
confidence: 99%